1993
DOI: 10.1037/0882-7974.8.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and processing stage on visual word recognition.

Abstract: The authors used a lexical-decision task in 3 different experiments to examine whether age differences in word recognition were consistent across processing stage. In all experiments, word frequency and length were manipulated. In Experiments 1 and 2, encoding difficulty was varied, and in Experiment 3, response selection difficulty was varied. In all 3 experiments, there were no age differences for word frequency. However, in Experiments 1 and 2, older adults showed a larger decrement for encoding. In Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
124
3
3

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(156 citation statements)
references
References 35 publications
26
124
3
3
Order By: Relevance
“…This has been taken as evidence for a decrease in the speed of processing with age. This view has received much support (e.g., Birren, 1965;Cerella, 1985Cerella, , 1990Cerella, Poon, & Williams, 1980;Fisk & Warr, 1996;Salthouse, 1985Salthouse, , 1996Salthouse, Kausler, & Saults, 1988) and much criticism and debate (Allen, Ashcraft, & Weber, 1992;Allen et al, 1993;Cerella, 1994;Fisk & Fisher, 1994;Fisher & Glaser, 1996;Hartley, 1992;Hertzog, 1992;Lima et al, 1991;Madden, 1989;Madden, Pierce, & Allen, 1992;Myerson et al, 1992;Myerson, Wagstaff, & Hale, 1994;Perfect, 1994). Ratcliff, Spieler, and McKoon (2000) argued against this view from a theoretical perspective by showing that in the frameworks of explicit models, there are multiple ways that slowing in mean RT can be produced, such as changes in the rate of accumulation of evidence, decision criteria settings, or both.…”
Section: Brinley Plotsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been taken as evidence for a decrease in the speed of processing with age. This view has received much support (e.g., Birren, 1965;Cerella, 1985Cerella, , 1990Cerella, Poon, & Williams, 1980;Fisk & Warr, 1996;Salthouse, 1985Salthouse, , 1996Salthouse, Kausler, & Saults, 1988) and much criticism and debate (Allen, Ashcraft, & Weber, 1992;Allen et al, 1993;Cerella, 1994;Fisk & Fisher, 1994;Fisher & Glaser, 1996;Hartley, 1992;Hertzog, 1992;Lima et al, 1991;Madden, 1989;Madden, Pierce, & Allen, 1992;Myerson et al, 1992;Myerson, Wagstaff, & Hale, 1994;Perfect, 1994). Ratcliff, Spieler, and McKoon (2000) argued against this view from a theoretical perspective by showing that in the frameworks of explicit models, there are multiple ways that slowing in mean RT can be produced, such as changes in the rate of accumulation of evidence, decision criteria settings, or both.…”
Section: Brinley Plotsmentioning
confidence: 99%
“…For example, Allen, Madden, and Crozier (1991) found average RTs of 800 ms for older adults compared with 500 ms for young adults. Word frequency effects, longer RTs with lower frequency words, are also larger for older adults (see Allen et al, 1991;Allen, Madden, Weber, & Groth, 1993;Allen, Sliwinski, & Bowie, 2002;Lima, Hale, & Myerson, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most dominant hypothesis has been the generalized slowing hypothesis, which states that all information processing is similarly affected by age (e.g., Birren, 1965;Brinley, 1965;Cerella, 1985Cerella, , 1990Cerella, , 1991Cerella, , 1994Fisk & Warr, 1996;Salthouse, 1985Salthouse, , 1996Salthouse, Kausler, & Saults, 1988). For some researchers, the general slowing hypothesis has been replaced by one that argues that different task domains show different degrees of slowing, for example, verbal versus spatial domains (see Allen, Ashcraft, & Weber, 1992;Allen, Madden, Weber, & Groth, 1993;Cerella, 1985Cerella, , 1994Hartley, 1992;Hertzog, 1992;Lima, Hale, & Myerson, 1991;Madden, 1989;Madden, Pierce, & Allen, 1992;Myerson, Ferraro, Hale, & Lima, 1992;Myerson, Wagstaff, & Hale, 1994;Perfect, 1994;Sliwinski & Hall, 1998). Whether general or domain specific, the slowing hypothesis has been favored by many cognitive aging researchers because it provides a relatively simple and intuitively appealing explanation of age-related decrements across a variety of laboratory tasks and everyday behaviors.…”
mentioning
confidence: 99%
“…Although the results of several studies indicate that older adults take significantly longer to recognize visually presented words than do younger adults (e.g., Allen, Madden, & Crozier, 1991;Bowles & Poon, 1981), Lima et al (1991) concluded that performance on lexical tasks (i.e., tasks utilizing words as stimuli) is less affected by age than is performance on nonlexical tasks. Allen et al (1993) reported that age differences in word recognition latencies may be due more to age decrements in peripheral processing stages rather than central processing stages. Using a lexical decision task, they found significant age differences for manipulations of stimulus encoding and response selection load but not PRECUING, AGE, AND TASK DEMANDS 949 for manipulations of word frequency, an index of lexical access.…”
mentioning
confidence: 99%